Mitos Tuk Budoyo dalam Tradisi Masyarakat Desa Losari Kabupaten Temanggung - Sri Prastiti Kusuma Anggraeni; Dandung Adityo Argo Prasetyo; Oktavia Putri Wijayanti (Keraton: Journal of History Education and Culture, 2026)
The existence of the Tuk Budoyo spring in Losari Village, Temanggung Regency, preserves mythological narratives that serve as the foundation of identity and social order for the local community. This research focuses on the historical background of the Tuk Budoyo tradition and its functional relevance amidst modernization. The study aims to describe the origins and development of the tradition while analyzing the functions of the myth as a mechanism for social control, cultural legitimacy, and local wisdom-based education. A qualitative method with descriptive and folkloristic approaches was employed, utilizing data from in-depth interviews with the juru kunci (custodian), village elders, community leaders, and local residents, supported by field documentation. Data analysis was conducted interactively through data collection, data condensation, data display, and conclusion drawing/verification based on the theory of folklore functions. Results indicate that the Tuk Budoyo myth possesses two variations of historical narratives reflecting cultural acculturation. The myth functions as a spiritual center, a means of legitimizing traditional arts, a tool for regulating social norms through customary rules, and a medium for environmental conservation. This study concludes that the Tuk Budoyo myth is not merely folklore but a life guide instilling moral values, environmental ethics, and humility, remaining relevant in maintaining the balance between humans, nature, and God. Therefore, this folklore has the potential to be integrated as local content teaching material in schools.